ESSENTIAL OIL OF OCIMUM GRATISSIUMUM AS SEED TREATMENT AGAINST SEED-BONE FUNGI OF SOYBEAN - Aoudou, YAOUBA; Childeric, ESSOLA ETOA Louis; Aurélie, NYAKA NGOBISA (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Antifungal activity of essential oil of Ocimum gratissimum against seed-borne fungi, the possible effect on seed germination and seedlings vigour were investigated. Five soybean seeds cultivars, naturally infected and collected from IRAD of Dschang and Foumbot, West Cameroon, were used. Soybean seeds were distributed among storage plastic, treated with essential oil (0 ; 2 ; 4 and 6 mg/mL) and stored for 40 days in storage conditions. Seed germination percentage, fungal seed infection and seedlings vigour were evaluated each 10 days of storage. Soybean seed treatment with essential oil of Ocimim gratissimum significantly reduce seed infection by fungi and also slightly improves soybean seed germination capacity for some cultivars. Non-significant reduction of germination level for ENGOPA 316 and HOULA 1 varieties treated with essential oil were observed. Soybean seedlings obtained from seeds treated with essential oil of O. gratissimum were more vigorous than those of untreated seeds. Essential oil of O. gratissimum for seed treatments may become a bio-fungicide for soybean protection